Real-world Roche Elecsys® and Fujirebio Lumipulse® inter-platform comparability and clinical validation of plasma neurofilament light chain in multiple sclerosis - Vincenzo Criscuolo; Valerio Nicolella; Carmela Polito; Rosa Sirica; Mariano Fiorenza; Domenica Sorvillo; Ilaria Delle Cave; Antonio Carotenuto; Maria Petracca; Roberta Lanzillo; Giuseppe Castaldo; Vincenzo Brescia Morra; et al. (Journal of Neurology, 2026)
Abstract Background Neurofilament light chain (NfL) reflects neuro-axonal injury in multiple sclerosis (MS), but method-dependent bias limits interchangeability across automated platforms. We assessed agreement between Roche Elecsys ® and Fujirebio Lumipulse ® , evaluated Simoa-referenced harmonization, validated Elecsys ® clinical associations, and derived directional IVD-to-IVD conversion models between Elecsys ® and Lumipulse ® . Methods In this retrospective real-world cohort ( N =253), fasting EDTA plasma was analyzed in singlicate on Elecsys ® and Lumipulse ® . Clinical associations of Elecsys ® pNfL were tested using multivariable linear models, including age, sex, disease duration, EDSS, cardiovascular comorbidities, smoking, and disease course, with sensitivity analyses including BMI. Results On the raw scale, platforms were strongly correlated but showed poor agreement (Coeff 6.91, 95% CI 6.44–7.38; r =0.879; CCC=0.107, 95% CI 0.090–0.123). After conversion of both assay outputs to published Simoa-equivalent values, alignment improved (Coeff 1.03, 95% CI 0.96–1.10). We derived a directional Elecsys ® -to-Lumipulse ® Passing–Bablok conversion (Lumipulse = 1.97 + 11.171 × Elecsys). Higher Elecsys ® pNfL was associated with disability (EDSS: Coeff 0.302, 95% CI 0.122–0.481; with BMI: Coeff 0.335, 95% CI 0.119–0.551) and was lower in treated versus untreated patients. Conclusions Elecsys ® and Lumipulse ® are not interchangeable on the raw pg/mL scale though conversion-based approaches can improve cross-platform alignment within the observed analytical range. Elecsys ® pNfL retained expected clinical associations, supporting routine MS use. Findings support cautious conversion during platform transitions in clinics.